2020
DOI: 10.1016/j.ijid.2019.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and spatiotemporal patterns of typhus group rickettsiosis at the county level in China, 2005–2017

Abstract: To explore the epidemiological characteristics and spatiotemporal patterns of typhus group rickettsiosis (TGR) in mainland China. Methods: A chi-squared test was used to compare the differences in the age and occupation distributions across the different years. Time-series analyses, spatial clustering analyses, and spatiotemporal scan statistics were used to detect the spatiotemporal patterns of the TGR incidence. Results: A total of 29,211 TGR cases were collected. Of these cases, 63.1% occurred from May to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There was the remarkable variation in the spatiotemporal distribution of scrub typhus cases in Fujian province, with most high-risk counties mainly concentrated in the Nanping and Zhangzhou prefecture and the geographical range of scrub typhus transmission increased over the study period, indicating that scrub typhus still remains a crucial public health problem. Both LISA and spatial distribution analysis detected similar changes and areas with high incidence appeared to shift from the south to the north mirroring the nationwide trends [ 10 , 23 , 43 ]. High-high spots which suggested that natural tsutsugamushi foci were forming here revealed the contribution of geography to the number of reported scrub typhus cases presumably in relation to elevated or mountainous region [ 44 ].…”
Section: Discussionmentioning
confidence: 90%
“…There was the remarkable variation in the spatiotemporal distribution of scrub typhus cases in Fujian province, with most high-risk counties mainly concentrated in the Nanping and Zhangzhou prefecture and the geographical range of scrub typhus transmission increased over the study period, indicating that scrub typhus still remains a crucial public health problem. Both LISA and spatial distribution analysis detected similar changes and areas with high incidence appeared to shift from the south to the north mirroring the nationwide trends [ 10 , 23 , 43 ]. High-high spots which suggested that natural tsutsugamushi foci were forming here revealed the contribution of geography to the number of reported scrub typhus cases presumably in relation to elevated or mountainous region [ 44 ].…”
Section: Discussionmentioning
confidence: 90%
“…Given that the power of quantitative statistics and mapping visualization, techniques of spatial epidemiological have been widely applied in infectious disease control, prevention, and scientific investigations [ 20 , 21 , 22 , 23 , 24 ]. As a vector-borne infectious disease, the distribution of ST has significant spatial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…and has been also widely conformed to characterize spatial epidemiology of diseases [14][15][16][17][18][19] . However, the dynamics spatiotemporal distributions of HFRS in Jiangxi have not yet been explored systematically.…”
mentioning
confidence: 99%